Application of geo-information technologies in determining the area of flooded lands as a result of the destruction of the Kakhovska HPP - Dorosh, Y.; Ibatullin, Sh.; Dorosh, O.; Sakal, О.; Dorosh, А. (Land Management, Cadastre and Land Monitoring, 2023)
Based on a sample of data from ministries, local authorities and other official open sources of information regarding the consequences of the destruction of the Kakhovska HPP dam and their analysis, it was found that they are inaccurate. Taking into account the above, the scientists of the Institute of Land Use of the National Academy of Sciences developed a methodology for determining the areas of flooded land affected by the destruction of the Kakhovska HPP dam, the territory under the Kakhovska Reservoir, which includes satellite images, geoinformation technologies, and artificial intelligence technologies. To identify and estimate the area of flooded land, satellite images were analysed before the terrorist attack and as of June 9, 2023, according to the results of which it was established that the total area of flooding according to the ESA WorldCover land cover classes was about 65 thousand hectares.Investigating the suitability for use of agricultural land for its intended purpose in the regions affected by the destruction, a land database with information on coordinates, intended purpose, form of ownership and other cadastre information was created from open sources of information.It was found that the number of land plots registered in the State Land Cadastre and located in the flooding zone is 30,325 plots. Other areas that are in the flooding zone are not registered. The total area of these areas affected by the flood is about 25 thousand hectares, including 9.8 thousand hectares (38%) - agricultural land. Only 20% of them are privately owned (three-quarters of them are agricultural land and one-quarter is land for residential and public development).It was established that the share of the area of land plots in the flooding zone in the total area by forms of ownership is: 56.5% - state property; 22.1% are communal, 20.3% are private, and 1.2% remain unspecified.Key words: Kakhovska reservoir, flooded lands, State Land Cadastre, geo-information technologies, artificial intelligence
Keywords: Kakhovska reservoir; flooded lands; State Land Cadastre; geo-information technologies; artificial intelligence